(untitled) (Historia, 2021)
1. Dahms, Hellmuth Gunther: Der zweite Weltkrieg 2. Van Jaarsveld, F. A. en Rademeyer, J. I.: Teorie en Metodiek vir Geskiedenisonderrig 3. Barry, Anna: Ons Japie 4. De Kersauson de Pennendreff, Robert: Ek en die Vierkleur 5. Rex, H. M.: Pretoria van Ketkplaas tot Regeringsetel 6. McBurney, C. M. B.: The Stone Age of Northern Africa 7. Welch, Galbriath: The Jet Lighthouse: An Account of Liberia 8. Myers, Edward D.: Education in the Perspective of History